Ecological drivers of spatial community dissimilarity, species replacement and species nestedness across temperate forests. Issue 5 (12th February 2018) - Wang, Xugao; Wiegand, Thorsten; Anderson‐Teixeira, Kristina J.; Bourg, Norman A.; Hao, Zhanqing; Howe, Robert; Jin, Guangze; Orwig, David A.; Spasojevic, Marko J.; Wang, Shunzhong; Wolf, Amy; Myers, Jonathan A.
Abstract: Aims: Patterns of spatial community dissimilarity have inspired a large body of theory in ecology and biogeography. Yet key gaps remain in our understanding of the local‐scale ecological processes underlying species replacement and species nestedness, the two fundamental components of spatial community dissimilarity. Here, we examined the relative influence of dispersal limitation, habitat filtering and interspecific species interactions on local‐scale patterns of the replacement and nestedness components in eight stem‐mapped temperate forest mega‐plots at different ontogenetic stages (large versus small trees). Location: Eight large (20–35 ha), fully mapped temperate forest plots in northern China and northern U.S.A. Time period: 2004–2016. Major taxa studied: Woody plants. Methods: We combined decomposition of community dissimilarity (based on the Ružička index) and spatial point‐pattern analysis to compare the spatial (i.e., distance‐dependent) replacement and nestedness components of each plot with that expected under five spatially explicit null models representing different hypotheses on community‐assembly mechanisms. Results: Our analyses revealed complex results. In all eight forests, spatial community dissimilarity was best explained by species replacement among local tree assemblages and by a null model based on dispersal limitation. In contrast, spatial nestedness for large and small trees was best explained by random placement and habitat filtering, respectively, in addition to dispersal limitation. However, interspecific interactions did not contribute to local replacement and nestedness. Main conclusions: Species replacement is the predominant process accounting for spatial community dissimilarity in these temperate forests and caused largely by local‐scale species clustering associated with dispersal limitation. Nestedness, in contrast, is less prevalent and primarily associated with larger variation in local species richness as caused by spatial richness gradients or 'hotspots' of local species richness. The novel use of replacement and nestedness measures in point pattern analysis is a promising approach to assess local‐scale biodiversity patterns and to explore their causes.